Integration of Anti-Sexual Violence Education with a Gender Equality Perspective to Strengthen Student Civic Engagement - Nurchotimah, Aulia Sholichah Iman; Sapriya, Sapriya; Nurbayani, Siti; Fitriasari, Susan (JED (Jurnal Etika Demokrasi), 2025)
The problem in this study is the existence of various cases of sexual violence and gender inequality that occur in the scope of education in higher education. Anti-sexual violence education is often not part of the mandatory curriculum. The large number of cases of sexual violence in tertiary institutions reflects the weakness of the prevention and treatment system, which has an impact on trauma, fear, and decreased student academic and social participation. This situation emphasizes the urgency of integrating anti-sexual violence education based on gender equality to strengthen student civic engagement in creating a safer and more inclusive campus environment. This research aims to develop the integration of anti-sexual violence educational material in the citizenship education curriculum to strengthen students' civic engagement in higher education. This study uses a descriptive qualitative approach. Qualitative research methods. This approach allows researchers to deeply understand the meaning, perceptions, and experiences of individuals related to the implementation of the material in learning. Data collection techniques were carried out through observations regarding learning and the citizenship education curriculum at UIN Siber Syekh Nurjati Cirebon, then conducting in-depth interviews with lecturers, students and related parties in the tertiary environment, as well as documentation studies of relevant campus policies. The number of participants in this research consisted of people, which included a group of participants, namely 7 students and 3 lecturers, campus policy maker. This study produces the concept of anti-sexual violence education in higher education based on gender equality, including; 1) anti-sexual violence material in higher education can be integrated through general compulsory courses, namely civic education, material on legal education is included in the domain of civic education. For this reason, the right material to be delivered is also related to the construction of sexual violence law. 2) Philosophy of learning theory as a basis for developing anti-sexual violence education to strengthen civic engagement in higher education; 3) Civic engagement of students in higher education can help efforts to overcome various phenomena of sexual violence. The conclusion of this study is that the integration of anti-sexual violence education in the curriculum is able to strengthen student awareness and involvement in efforts to prevent sexual violence. Suggestions from the study must be real and consistent implementation from various parties to participate in overcoming sexual violence, especially in the educational environment.